ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT ALUMNI PONDOK PESANTREN DAAR EL-QOLAM DALAM MEMILIH ASURANSI SYARIAH - Firyal Nida Aulia Sholihah; Hanafi Hanafi (Syar'Insurance: Jurnal Asuransi Syariah, 2019)
Human life in this world in principle will not be separated from various needs and problems, be it primary, secondary or tertiary needs, which all require effective problem solving. One example of these needs and problems is health and mental problems which all lead to one threat that is reducing or eliminating financial capacity. Based on the background above, the formulation of the problem in this study are: 1). What are the factors that influence the interest of Daar El-Qolam Islamic Boarding School alumni in choosing Islamic insurance? 2.) Can Product, Price, Location, Promotion and Religiosity Factors influence the interest of Daar El-Qolam Islamic Boarding School alumni in choosing Islamic insurance? The purpose of this study is: to determine the factors that influence the interest of alumni Daar El-Qolam Islamic Boarding School in choosing Islamic insurance. The data used are primary data that is the results of this research questionnaire using the validity test, the reliability test, the classical assumption test with the help of the use of the SPSS 21 program. X3 was 2,578, Xitung was 4,789 and X5 was 2,562. The value of ttable by using a significant level α = 5% df (nk-1) = (81-5-1) = 75 then the size of ttable = 1.99210 so tcount X1, X2, X3, X4 and X5> (3,835, 3,267, 2,578, 4,789, 2,562> 1,99210) and such a significant level Ha is accepted and Ho is rejected. This means that partially the independent variables X1, X2, X3, X4, and X5 (0.006, 0.000, 0.005, 0.008, and 0.012) are smaller than 0.05. with that product, price, location, promotion, religiosity has a significant effect on the dependent variable namely Alumni Interest in Daar El-Qolam Islamic Boarding School. The coefficient of determination performed on the determination test obtained by the square value shows that the product, price, location, promotion, religiosity. Can explain its effect on the interest of alumni of Islamic insurance, which is 30.3%. while the remaining 69.7% is influenced by other variables outside the Daar El-Qolam Islamic Boarding School Alumni Interest.